Acceptability of optimized fresh moringa oleifera and soymilk beverage - Raouf Tonyi Mensah; Mamy Eklou-Lawson; Banfitebiyi Gambogou; Messanh Kangni-Dossou; Yaovi Ameyapoh (CyTA - Journal of Food)
The objective of this study is to optimise a soymilk beverage that is well received by consumers. In the initial sensory evaluation, forty panelists were required to establish their preference between two soymilk beverages prepared from ungerminated and germinated soybeans. The ungerminated soymilk (SM) is preferred to the germinated one (GSM) due to the unfavourable taste and overall acceptability induced by the germination process. An enrichment of the SM was conducted with moringa leaf extract at varying ratios (10–30%) and was evaluated for its sensory properties. The optimal ratio of 85% SM and 15% moringa extract, as determined by sensory evaluation, was validated by 81% of the 80 panelists as acceptable in terms of colour, taste, and overall acceptance. In terms of its nutritional composition, the beverage is comparable to cow’s milk and, can be recommended as an alternative for individuals who are lactose intolerant to cow’s milk.